Physical rehabilitation based on kinect serious games: ThG therapy game - Ferreira, Diogo Veiga (2017)
This thesis presents a serious game platform developed using Unity 3D game Engine and Kinect V2 sensor as a natural user interface. The aim of this work was to provide a tool for objective evaluation of patients’ movements during physiotherapy sessions as well as a pleasant way that may increase patient engagement on training motor rehabilitation exercises. The developed platform based on Kinect V2 sensor detects 3D motion of different body joints and provides data storage capability in a remote database. The platform for patient’s data management during physiotherapy process includes biometric data, some data relevant for physiotherapist related to patient’s clinical history, obtained scores during serious game based training and values of metrics such as the distance between feet during a game, left and right feet usage frequency and execution time for imposed movement associated with game mechanics. A description of technologies and techniques used for development of the platform and some results related to usability of the platform are presented in this thesis.